2016
DOI: 10.1177/0300060515621639
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of intravenous midazolam and ketamine on emergence agitation in children: Randomized controlled trial

Abstract: ObjectiveA prospective, double-blind, randomized controlled trial to compare the effect of preoperative midazolam or ketamine on the incidence of emergence agitation (EA) following sevoflurane anaesthesia in children.MethodsPaediatric patients (2–6 years old) undergoing ophthalmic surgery were allocated to receive premedication with either 0.1 mg/kg midazolam or 1 mg/kg ketamine. Incidence of EA and postoperative pain scores were recorded at 10-min intervals in the postanaesthetic care unit (PACU). The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
(38 reference statements)
0
22
2
Order By: Relevance
“… 22 reported that thiopental sodium and ketamine used as anesthetic induction agents in children undergoing ophthalmic surgery showed a similar incidence of EA. 22 However, other studies reported that ketamine premedication 23 or intraoperative use of ketamine 24 were effective in preventing EA.…”
Section: Discussionmentioning
confidence: 98%
“… 22 reported that thiopental sodium and ketamine used as anesthetic induction agents in children undergoing ophthalmic surgery showed a similar incidence of EA. 22 However, other studies reported that ketamine premedication 23 or intraoperative use of ketamine 24 were effective in preventing EA.…”
Section: Discussionmentioning
confidence: 98%
“…may decrease the incidence of early EA (first 20 min) more effectively than midazolam 0.1 mg kg À1 i.v. 66 Premedication with ketamine (6 mg kg À1 orally 30 min before induction) has also been effective in decreasing EA from 56 to 18% after desflurane for adenotonsillectomy. 67 Intraoperative ketamine (1 mg kg À1 i.v.…”
Section: Ketaminementioning
confidence: 99%
“…Meanwhile, ketamine has been safely used in pediatric anesthesia for over five decades. It effectively decreased the incidence of emergence delirium in previous studies [ 23 , 24 ]. Moreover, it was equally effective as dexmedetomidine in a study after strabismus surgery with sevoflurane [ 25 ].…”
Section: Discussionmentioning
confidence: 82%